2017
DOI: 10.21608/ejchem.2017.541.1001
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Textile Finishes – Natural Antibacterial Finishes for Cotton Fabric.

Abstract: IMPROVEMENT of physical properties in an addition to imparting antimicrobial properties to cotton fabric and modified cotton fabric by using herbal in the presence of softeners is the target of the present work, first of all modification of cotton fabric was done during cationization process by the means of cationized agent, namely, 3-chloro-2-hydroxypropyl trimethyl ammonium chloride (Quat-188); also, cotton fabric was modified during carboxymethylation process of it. Then treatments of cotton and modified co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…[3] Natural biocides include essential oils and plant extracts that can be used as antimicrobial finishing agents in textile manufacturing, their advantages include being non-toxic, non-allergic, and not causing microbial resistance. [42]…”
Section: Environmental Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Natural biocides include essential oils and plant extracts that can be used as antimicrobial finishing agents in textile manufacturing, their advantages include being non-toxic, non-allergic, and not causing microbial resistance. [42]…”
Section: Environmental Impactmentioning
confidence: 99%
“…Neem's medicinal effect can help with skin, cough, and lung diseases. [42] recently a limited number of studies have already shown neem's use in textiles as an antibacterial agent and have evaluated its antimicrobial property. cotton and cotton/polyester blended fabric have been used in these studies.…”
Section: Neem (Azadirachta Indica)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, awareness of green chemistry and adoption of new sustainable technologies such as bio‐, nano‐, and plasma‐technologies to meet the ever‐growing consumer's demands, revived the development of the environmentally benign textile wet processes and implementation of cleaner production opportunities 4‐7 . Among the emerging technologies, potential applications of bio‐finishing using enzymes, biopolymers and aromatherapy to add special functionalities to textile products without adverse effect on the products and ecology are growing fast 8‐15 . Sustainable textile chemical processes and high quality multi‐functionalised green textile products can lead to high added‐value and additional marketing advantages 16‐18 …”
Section: Introductionmentioning
confidence: 99%
“…Due to their eco-friendly nature, it has a higher% of acceptance in the market. These antibacterial extracts can be used as the textile finishing agents in the solvent [7].…”
Section: Introductionmentioning
confidence: 99%